Colonel Effingham's raid - Fleming, Berry, 1899-1989 (Duell, Sloan & Pearce, 1943)
"Set in 1940 Georgia, [this book] is the story of W. Seaborn Effingham, Colonel U.S. Army, retired, who returns to his home town of Fredericksville. The colonel offers to write a weekly column for a local paper, covering the war in Europe. But after many years away from Fredericksville, Effingham doesn't understand how its citizens have abdicated all government to a small, one-party clique, the Home Folks Party. In his colorful, detailed account of Revolutionary and Civil War local history, with occasional attention paid to the growing World War, the Colonel's column stirs up the powers that be. The community is split over whether to renovate or tear down the town courthouse, and there's a showdown in which Effingham is a catalyst. Fleming's barbs seem gentle, but they go deep in this delightful satire as we watch the odd, single-minded, thoroughly upstanding Colonel bring to bear the forces of honesty and common sense. Although the ending isn't officially a victory for him, Effingham really does win"